GC-IMS and olfactometry analysis on the tea aroma of Yingde black teas harvested in different seasons. (December 2021) - Liu, Haocheng; Xu, Yujuan; Wu, Jijun; Wen, Jing; Yu, Yuanshan; An, Kejing; Zou, Bo
Graphical abstract: Highlights: Establishment of volatile fingerprint of among samples were revealed by GC-IMS. The twenty most aroma-active compounds were identified by GC-O-MS. Systematic analysis of the change trend of among samples by precursor substances. Aroma characteristics of black tea in different picking seasons were confirmed by PLSR. Abstract: This study aims to investigate the influence of different harvesting seasons on the aroma of black tea and the trend in the tea aroma variation. A total of 68 volatile substances was identified by gas chromatography coupled with ion-mobility spectrometry (GC-IMS), and 20 characteristic aroma-active compounds were quantitatively analyzed by gas chromatography-olfactometry coupled with aroma extract dilution analysis (GC-O AEDA) and odor activity value (OAV) analysis. These aroma-active compounds are mainly linalool, β-damascenone, and benzeneacetaldehyde. Both methods confirmed that the aroma of tea changes with the harvesting seasons, showing a downward trend followed by an upward trend. Besides, black teas harvested in different seasons have their characteristic volatile compounds and metabolism precursors. The degradation of glycosides, carotenes, and amino acids are the most important degradation pathways for the formation of tea aroma. The PLSR results of GC-O-AEDA, OAV, and DSA data agree with each other, showing that five aroma attributes of the autumn tea have strong correlations. The autumn tea has the richest aroma, followed by the spring tea and the summer tea.